A bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber
By combining the interface between fluorosilane grafted modified carbon fiber and polytetrafluoroethylene, combined with lubricating fillers and functional fillers, the problem of lubrication failure of polytetrafluoroethylene composite materials during friction is solved, and bearing lubricating materials with high wear resistance, low friction coefficient and high heat conductivity are achieved, extending the service life of the bearing.
Patent Information
- Application Number
- CN202310769764.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-06-28
AI Technical Summary
The PTFE composite material fails lubrication during friction due to pressure deformation, thermal deformation and wear, and it is difficult to establish a strong bonding and tight interface with functional fillers, which limits its comprehensive performance improvement.
Through fluorosilane grafting modified carbon fiber, the interface combination between carbon fiber and polytetrafluoroethylene is enhanced, and lubricating fillers and functional fillers are combined. Bearing lubricating materials with high wear resistance, low friction coefficient, creep resistance and high heat conductivity are prepared by mechanical blending, cold pressing and pre-pressing, sintering and molding.
It significantly improves the mechanical strength, tribological properties, thermal conductivity and dimensional stability of composite materials, and extends the service performance and service life of bearings.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a lubricating material, in particular to a bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber, which is mainly used for polymer / metal composite sliding bearings and belongs to the field of composite materials and bearings. Background Art
[0002] Polymer / metal composite sliding bearings are self-lubricating bearings with excellent performance made by embedding or bonding polymer composite materials in a metal matrix. They are widely used in aerospace and marine engineering fields under harsh working conditions such as heavy loads, high speeds, high and low temperatures, and corrosion. Polymers are the core materials for bearings to achieve wear-resistant and lubricating functions, and are mostly based on self-lubricating, corrosion-resistant, and highly flexible polytetrafluoroethylene resins. However, due to the inherent characteristics of polytetrafluoroethylene, such as easy creep, poor wear resistance, and insufficient thermal conductivity, composite bearings often fail to lubricate due to pressure deformation, thermal deformation, and wear during friction. In recent years, the wear resistance, heat resistance, load-bearing capacity, and dimensional stability of polytetrafluoroethylene resins have been improved to a considerable extent by introducing functional fillers such as inorganic fibers, carbon materials, metal oxides, and polymers of different sizes. However, due to the highly inert chemical properties and extremely high melt viscosity of polytetrafluoroethylene, it is difficult for polytetrafluoroethylene to establish strong chemical bonds with functional fillers, and it is also difficult to fully infiltrate the fillers through resin melt flow and thus establish a close interface bond with the fillers at the physical level. This is the main problem that limits the improvement of the comprehensive performance of polytetrafluoroethylene composites.
[0003] Carbon fiber is one of the main functional fillers used to enhance the strength and wear resistance of polymers. The use of silane coupling agent or titanate coupling agent to graft and modify carbon fiber has been proven to be an effective technical means to enhance the interfacial bonding strength between fillers and polymers and improve the comprehensive performance of composite materials. Introducing an appropriate proportion of carbon fiber into thermosetting resins and thermoplastic resins such as polyoxymethylene, polyetheretherketone, and polyimide can effectively improve the strength, wear resistance, dimensional stability, and service life of composite materials. However, the surface of this type of coupling agent is mostly polar groups such as amino, hydroxyl, carboxylic acid, and mercapto groups, which are not very effective in improving the comprehensive performance of carbon fiber / polytetrafluoroethylene composite materials. When used in the lubrication parts of embedded and cushioned polytetrafluoroethylene / metal composite sliding bearings, their service performance and service life are not ideal. Summary of the invention
[0004] The purpose of the present invention is to provide a bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber in order to solve the problem that the comprehensive performance of polytetrafluoroethylene composite materials in the existing bearing lubrication technology is not ideal. The interface bonding between carbon fiber and polytetrafluoroethylene is improved by fluorosilane grafting modification to obtain a polytetrafluoroethylene bearing lubricating material with high wear resistance, low friction coefficient, creep resistance and high thermal conductivity. The polytetrafluoroethylene bearing lubricating material is applied to the lubricating parts of inlaid and liner type polytetrafluoroethylene / metal composite sliding bearings to improve their service performance and service life.
[0005] 1. Preparation of polytetrafluoroethylene bearing lubricating materials
[0006] The bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber of the present invention is obtained by mechanical blending, cold pressing pre-pressing and sintering by using modified polytetrafluoroethylene resin as polymer matrix, fluorosilane modified carbon fiber as reinforcing filler, lubricating filler and functional filler as modified components. The raw materials are calculated by the following volume parts: 85-95 parts of modified polytetrafluoroethylene resin, 2-8 parts of fluorosilane modified carbon fiber, 0.5-2 parts of lubricating filler and 0.1-1 parts of functional filler.
[0007] The preparation of the modified polytetrafluoroethylene resin is to use perfluoromethyl vinyl ether, perfluorovinyl ether or perfluoropropyl vinyl ether as a modified monomer and peroxide malonic acid as an initiator. Under the working conditions of 60-90°C and 900-1300kPaA, tetrafluoroethylene monomer and modified monomer are polymerized for 1-5 hours to obtain modified polytetrafluoroethylene resin. The mechanism of modified polytetrafluoroethylene resin is to polymerize tetrafluoroethylene monomer and modified monomer through free radicals generated by decomposition of peroxide malonic acid under the working conditions of 60-90°C and 900-1300kPaA to obtain modified polytetrafluoroethylene resin. The added amount of modified monomer is 1-10% of the volume of tetrafluoroethylene monomer, and the added amount of initiator peroxide malonic acid is 1-3% of the volume of tetrafluoroethylene monomer. The tensile strength of the obtained polytetrafluoroethylene modified resin is 35-45MPa, and the particle size is 25-35μm. The introduction of a small amount of modified monomers increases the irregularity and flexibility of the polytetrafluoroethylene molecular chain, greatly improving its processing performance.
[0008] The preparation of the fluorosilane-modified carbon fiber is as follows: disperse the carbon fiber raw material in ethanol, add an activator and react for 3 to 180 minutes, filter out the carbon fiber and dry it; then disperse the activated carbon fiber in a mixed solution of n-butanol-deionized water and adjust the solution pH to 2 to 4, then add fluorosilane, react for 2 to 36 hours under the conditions of an ultrasonic frequency of 5 to 40 kHz and a temperature of 25 to 120°C; after the reaction is completed, filter and dry to obtain the fluorosilane-modified carbon fiber. The carbon fiber raw material is one or more of asphalt-based carbon fiber, polyacrylonitrile-based carbon fiber and vapor-phase carbon fiber, the carbon fiber diameter is 7 μm, the aspect ratio is 5 to 20, and the thermal conductivity is 500 to 1500 W / (m·K). The activator is one of acetic acid, nitric acid, sulfuric acid and hydrochloric acid, and the amount of the activator added is 5-50% of the volume of the carbon fiber raw material; in the mixed solution of n-butanol-deionized water, the volume ratio of n-butanol to deionized water is 7.5:1-9.5:1; the fluorosilane is one or more of trifluoropropylmethyldimethoxysilane, trifluoropropyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorooctyltriethoxysilane, perfluorodecyltriethoxysilane and heptadecafluorodecyltriethoxysilane, and the amount of the fluorosilane added is 1-25% of the volume of the carbon fiber. After activation treatment and fluorosilane grafting modification of the carbon fiber, the interface bonding between the carbon fiber and the polytetrafluoroethylene resin is improved, thereby further improving the strength, wear resistance, thermal conductivity and dimensional stability of the composite material.
[0009] The lubricating filler is one or more of graphite fluoride, molybdenum disulfide, polyetheretherketone, and polyimide; the size of the lubricating filler is 0.05-60 μm. The functional filler is one or more of aluminum oxide, aluminum nitride, carbon powder, boron nitride, nickel oxide, and silicon carbide; the size of the functional filler is 20-500 nm. By introducing lubricating fillers and functional fillers and filling them with low content, the friction coefficient, wear rate, and thermal conductivity of the composite material can be regulated on the basis of ensuring high tensile strength and elongation of the composite material.
[0010] The mechanical blending is carried out in a double-shaft mixer, the shearing knife speed of the stirring kettle is 200-4000 rpm, the overall speed of the stirring kettle around the cantilever is 2-50 rpm, and the mixing time is 1-30 min. Low-temperature double-shaft blending is used to avoid heating and bonding of polytetrafluoroethylene during mechanical stirring.
[0011] The cold pre-pressing is carried out in a steel mold with upper and lower bidirectional loading, with a pressing pressure of 25-45 MPa and a holding time of 3-20 minutes. The uniformity of the molding material is improved by bidirectional pressing.
[0012] The sintering is carried out in a special polytetrafluoroethylene sintering furnace equipped with a rotating tray, the sintering temperature is 360-390° C., the time is 30-240 min, and the tray rotation speed is 5-50 rpm.
[0013] 2. Performance test of polytetrafluoroethylene bearing lubricating materials
[0014] 1. Friction and wear performance test
[0015] The test method is as follows: According to ASTM G99-05, the polytetrafluoroethylene bearing lubricant material molded product is processed into a block specimen with a size of 19mm×12mm×12mm, matched with a 316 stainless steel ring, and tested in an MRH-3 high-speed ring-block friction and wear tester; the test contact load is 50N, the linear speed is 0.5m / s, and the running time is 30min; the friction coefficient is automatically recorded and output by the tester, and the wear rate is calculated by the mass loss of the sample before and after wear.
[0016] 2. Tensile strength test
[0017] The test method is: mechanical processing into the national standard specified size and conducting mechanical property test on a universal testing machine. The tensile strength specimen is a dumbbell shape of 80 mm×10 mm×4 mm. The test standard is GB / T 1040.2-2006, and the tensile rate is 100 mm / min.
[0018] 3. Thermal conductivity test
[0019] The test method is: machine it into a disc shape of φ100mm×5mm, and test it on a thermal conductivity tester according to GB / T3139-2005.
[0020] 4. Test results
[0021] The modified polytetrafluoroethylene bearing lubricating material prepared by the present invention has a tensile strength of 25-32 MPa, a friction coefficient of 0.02-0.10, and a wear rate of (0.5-2) × 10 -5 mm 3 / Nm, thermal conductivity 0.3~0.5 W / (m·K). It can be seen that the modified polytetrafluoroethylene lubricating material has excellent mechanical strength and thermal conductivity, and has a low friction coefficient and wear rate when used as a lubricating material, and is particularly suitable for the manufacture of polymer self-lubricating bearings.
[0022] In summary, the present invention uses modified polytetrafluoroethylene resin as a polymer matrix, fluorosilane-modified carbon fiber as a main reinforcing filler, and a small amount of lubricating filler and functional filler as a modified component, and is prepared through mechanical blending, pre-pressing, sintering and other processes. The polytetrafluoroethylene resin is polymerized and modified, so that its processing performance is greatly improved on the basis of maintaining the original physical and chemical properties of polytetrafluoroethylene; the carbon fiber is activated and grafted with fluorosilane to improve the interface bonding between the carbon fiber and the polytetrafluoroethylene resin; on this basis, combined with the introduction of lubricating fillers and functional fillers and the control of component content, the mechanical strength, tribological properties, thermal conductivity and dimensional stability of the composite material are comprehensively improved, and the application of the inlaid type and liner type polytetrafluoroethylene / metal composite sliding bearing lubrication components can effectively improve their service performance and service life. DETAILED DESCRIPTION
[0023] The modified polytetrafluoroethylene bearing lubricating material of the present invention, its preparation method and performance are further described below through specific examples.
[0024] Example 1
[0025] (1) Preparation of modified polytetrafluoroethylene: 1% by volume of modified monomer perfluoropropyl vinyl ether and 2% peroxymalonic acid were added to tetrafluoroethylene monomer, and the mixture was reacted at 85°C and 1100 kPaA for 3 h to obtain modified polytetrafluoroethylene resin;
[0026] (2) Preparation of modified carbon fiber: 50 g of polyacrylonitrile-based carbon fiber (diameter 7 μm, aspect ratio 8, thermal conductivity 800 W / (m·K)) was dispersed in 500 g of ethanol, and then 13.4 mL of acetic acid was added and activated for 150 min. The carbon fiber was filtered and dried at 80 °C for 2 h. 40 g of the activated carbon fiber was dispersed in 500 mL of a mixed solution of n-butanol / deionized water (volume ratio of n-butanol / deionized water was 9:1), and the pH value of the solution was adjusted to 3.0. Then 2 g of perfluorodecyltrimethoxysilane was added, and the reaction was carried out at an oscillation frequency of 20 kHz and a temperature of 100 °C for 24 h, and then filtered and dried to obtain 35 g of fluorosilane-grafted modified carbon fiber.
[0027] (3) Blending of resin and filler: 950 g of modified polytetrafluoroethylene resin, 30 g of fluorosilane grafted modified carbon fiber, 10 g of fluorinated graphite (size 15 μm) and 10 g of aluminum nitride (size 300 nm) were placed in a biaxial mixer and mixed for 5 min. The shear cutter speed of the stirred tank was 500 rpm, and the overall speed of the stirred tank around the cantilever was 5 rpm;
[0028] (4) Pre-pressing and sintering: Take 212g of the blended raw material, add it into a steel mold with a diameter of 120mm, apply a bidirectional pressure of 40MPa, and maintain it for 10min to obtain a pre-pressed blank with a diameter of 120mm and a thickness of 8mm. Then place the blank on the rotating tray of a special sintering furnace for polytetrafluoroethylene, set the tray speed to 20rpm, sinter at 375℃ for 120min, and obtain the polytetrafluoroethylene bearing lubricant after cooling. The properties of the polytetrafluoroethylene bearing lubricant are shown in Table 1.
[0029] Example 2
[0030] (1) Preparation of modified polytetrafluoroethylene: 2% by volume of modified monomer perfluorovinyl ether and 1% peroxymalonic acid were added to tetrafluoroethylene monomer, and the mixture was reacted at 80°C and 1200 kPaA for 4 h to obtain modified polytetrafluoroethylene resin;
[0031] (2) Preparation of modified carbon fiber: 100 g of polyacrylonitrile-based carbon fiber was dispersed in 1000 g of ethanol, followed by adding 3 mL of nitric acid and activating the reaction for 10 min; the carbon fiber was filtered and dried at 80 °C for 2 h; 90 g of the activated carbon fiber was dispersed in 1000 ml of a mixed solution of n-butanol / deionized water (the volume ratio of n-butanol to deionized water was 99.5:1), and the pH value of the solution was adjusted to 2.0; then 2 g of perfluorooctyltriethoxysilane was added and reacted at an oscillation frequency of 35 kHz and a temperature of 1200 °C for 12 h; 85 g of fluorosilane-grafted modified carbon fiber was obtained by filtering and drying;
[0032] (3) Blending of resin and filler: 900 g of modified polytetrafluoroethylene resin, 70 g of fluorosilane grafted modified carbon fiber, 20 g of molybdenum disulfide (size 20 μm) and 10 g of carbon powder (size 50 nm) were placed in a double-shaft mixer and mixed for 5 min. The shear cutter speed of the stirred tank was 400 rpm, and the overall speed of the stirred tank around the cantilever was 10 rpm;
[0033] (4) Pre-pressing and sintering: Take 515g of the blended raw material, add it into a steel mold with a diameter of 120mm, apply a bidirectional pressure of 35MPa, and maintain it for 15min to obtain a pre-pressed blank with a diameter of 150mm and a thickness of 12mm. Then place the blank on the rotating tray of a special sintering furnace for polytetrafluoroethylene, set the tray speed to 20rpm, sinter at 380℃ for 120min, and obtain the polytetrafluoroethylene bearing lubricant after cooling. The properties of the polytetrafluoroethylene bearing lubricant are shown in Table 1.
[0034] Example 3
[0035] (1) Preparation of modified polytetrafluoroethylene: 3% by volume of perfluoromethyl vinyl ether and 1.5% of peroxymalonic acid were added to tetrafluoroethylene monomer, and the mixture was reacted at 90°C and 1300 kPaA for 3.5 hours to obtain modified polytetrafluoroethylene resin;
[0036] (2) Preparation of modified carbon fiber: 50 g of gas-phase carbon fiber was dispersed in 500 g of ethanol, and then 13.4 mL of acetic acid was added and activated for 150 min; the carbon fiber was filtered and dried at 80 °C for 2 h; then 40 g of the activated carbon fiber was dispersed in a mixed solution of n-butanol / deionized water (volume ratio of n-butanol / deionized water was 9:1), and the pH value of the solution was adjusted to 3.0; then 2 g of perfluorodecyltrimethoxysilane was added, and the reaction was carried out at an oscillation frequency of 20 kHz and a temperature of 100 °C for 24 h, and then filtered and dried to obtain 35 g of fluorosilane-grafted modified carbon fiber;
[0037] (3) Blending of resin and filler: 910 g of polytetrafluoroethylene modified resin, 70 g of fluorosilane grafted modified carbon fiber, 15 g of polyetheretherketone (size 50 μm) and 5 g of silicon carbide (size 50 nm) were placed in a double-shaft mixer and mixed for 15 min. The shear cutter speed of the stirring kettle was 1000 rpm, and the overall speed of the stirring kettle around the cantilever was 35 rpm;
[0038] (4) Pre-pressing and sintering: Take 25g of the blended raw material, add it into a steel mold with a diameter of 80mm, apply a bidirectional pressure of 35MPa, and maintain it for 5min to obtain a pre-pressed blank with a diameter of 80mm and a thickness of 2mm. Then place the blank on the rotating tray of a special sintering furnace for polytetrafluoroethylene, set the tray speed to 45rpm, sinter at 375℃ for 120min, and obtain the polytetrafluoroethylene bearing lubricant after cooling. The properties of the polytetrafluoroethylene bearing lubricant are shown in Table 1.
[0039]
[0040] Comparative Example 1
[0041] (1) Preparation of modified polytetrafluoroethylene: same as in Example 1;
[0042] (2) Blending of resin and filler: 950 g of modified polytetrafluoroethylene resin, 30 g of polyacrylonitrile-based carbon fiber, 10 g of fluorinated graphite (size 15 μm) and 10 g of aluminum nitride (size 300 nm) were placed in a biaxial mixer and mixed for 5 min. The shear cutter speed of the stirring kettle was 500 rpm, and the overall speed of the stirring kettle around the cantilever was 5 rpm;
[0043] (3) Pre-pressing and sintering: Take 212g of the blended raw material, add it into a steel mold with a diameter of 120mm, apply a bidirectional pressure of 40MPa, and maintain it for 10min to obtain a pre-pressed blank with a diameter of 120mm and a thickness of 8mm. Then place the blank on the rotating tray of a special sintering furnace for polytetrafluoroethylene, set the tray speed to 20rpm, sinter at 375℃ for 120min, and obtain the polytetrafluoroethylene bearing lubricant after cooling. The properties of the bearing lubricant are shown in Table 2.
[0044] By comparing Example 1 with Comparative Example 1, it can be seen that when the carbon fiber is not modified with fluorosilane, the tensile strength of the composite material decreases to 20 MPa, and the wear rate increases to 3×10 -5 mm 3 / N·m.
[0045] Comparative Example 2
[0046] (1) Preparation of modified carbon fiber: same as Example 2;
[0047] (2) Blending of resin and filler: 900 g of polytetrafluoroethylene resin, 70 g of fluorosilane grafted modified carbon fiber, 20 g of molybdenum disulfide (size 20 μm) and 10 g of carbon powder (size 50 nm) were placed in a double-shaft mixer and mixed for 5 min; the shear cutter speed of the stirring kettle was 400 rpm, and the overall speed of the stirring kettle around the cantilever was 10 rpm;
[0048] (3) Pre-pressing and sintering: Take 515g of the blended raw material, add it into a steel mold with a diameter of 120mm, apply a bidirectional pressure of 35MPa, and maintain it for 15min to obtain a pre-pressed blank with a diameter of 150mm and a thickness of 12mm. Then place the blank on the rotating tray of a special sintering furnace for polytetrafluoroethylene, set the tray speed to 20rpm, sinter at 380℃ for 120min, and cool it to obtain a polytetrafluoroethylene bearing lubricant. The properties of the bearing lubricant are shown in Table 2.
[0049] By comparing Example 2 with Comparative Example 2, it can be seen that without using modified polytetrafluoroethylene resin as the matrix, the tensile strength of the composite material decreases to 23 MPa, while the wear rate increases to 2.2×10 -5 mm 3 / N·m.
[0050] Comparative Example 3
[0051] (1) Preparation of modified carbon fiber: same as Example 2;
[0052] (2) Blending of resin and filler: 900 g of polytetrafluoroethylene resin, 90 g of fluorosilane grafted modified carbon fiber and 10 g of carbon powder (size 50 nm) were placed in a biaxial mixer and mixed for 15 min; the shear cutter speed of the stirring kettle was 400 rpm, and the overall speed of the stirring kettle around the cantilever was 10 rpm;
[0053] (3) Pre-pressing and sintering: Take 515g of the blended raw material, add it into a steel mold with a diameter of 120mm, apply a bidirectional pressure of 35MPa, and maintain it for 15min to obtain a pre-pressed blank with a diameter of 150mm and a thickness of 12mm. Then place the blank on the rotating tray of a special sintering furnace for polytetrafluoroethylene, set the tray speed to 20rpm, sinter at 380℃ for 120min, and cool it to obtain a polytetrafluoroethylene bearing lubricant. The properties of the bearing lubricant are shown in Table 2.
[0054] By comparing Example 2 with Comparative Example 3, it can be seen that without adding lubricating filler, the friction coefficient of the composite material increases to 0.12 and the wear rate increases to 3.5×10 -5 mm 3 / N·m.
[0055] Comparative Example 4
[0056] (1) Preparation of modified polytetrafluoroethylene: same as in Example 1;
[0057] (2) Blending of resin and filler: 960 g of polytetrafluoroethylene modified resin, 30 g of polyacrylonitrile-based carbon fiber, and 10 g of fluorinated graphite (size 15 μm) were placed in a double-shaft mixer and mixed for 15 min. The shear cutter speed of the stirring kettle was 500 rpm, and the overall speed of the stirring kettle around the cantilever was 5 rpm.
[0058] (3) Pre-pressing and sintering: Take 212g of the blended raw material, add it into a steel mold with a diameter of 120mm, apply a bidirectional pressure of 40MPa, and maintain it for 10min to obtain a pre-pressed blank with a diameter of 120mm and a thickness of 8mm. Then place the blank on the rotating tray of a special sintering furnace for polytetrafluoroethylene, set the tray speed to 20rpm, sinter at 375℃ for 120min, and cool it to obtain a polytetrafluoroethylene bearing lubricant. The properties of the bearing lubricant are shown in Table 2.
[0059]
[0060] By comparing Example 1 and Comparative Example 4, it can be seen that when no functional filler is added, the thermal conductivity of the composite material decreases to 0.28 W / (m·K).
[0061] The materials and reagents used in the above examples and comparative examples are all commercially available. The tensile strength of the polytetrafluoroethylene modified resin is 35-45 MPa, and the particle size is 25-35 μm; the carbon fiber diameter is 7 μm, the aspect ratio is 5-20, and the thermal conductivity is 500-1500 W / (m·K); the fluorosilane modification step is completed in an ultrasonic oscillator.
Claims
1. A bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber, which is obtained by mechanical blending, cold pre-pressing and sintering with modified polytetrafluoroethylene resin as a polymer matrix, fluorosilane modified carbon fiber as a reinforcing filler, and lubricating filler and functional filler as modified components; each raw material is calculated by the following volume parts: 85-95 parts of modified polytetrafluoroethylene resin, 2-8 parts of fluorosilane modified carbon fiber, 0.5-2 parts of lubricating filler, and 0.1-1 parts of functional filler; The preparation method of the modified polytetrafluoroethylene resin is to use perfluorovinyl ether as a modified monomer and peroxymalonic acid as an initiator, and to polymerize tetrafluoroethylene monomer and modified monomer for 1 to 5 hours under the working conditions of 60 to 90° C. and 900 to 1300 kPa to obtain the modified polytetrafluoroethylene resin; The amount of the modified monomer added is 1-10% of the volume of the tetrafluoroethylene monomer, and the amount of the initiator peroxymalonic acid added is 1-3% of the volume of the tetrafluoroethylene monomer; the perfluorovinyl ether is perfluoromethyl vinyl ether or perfluoropropyl vinyl ether; The preparation method of the fluorosilane-modified carbon fiber is as follows: dispersing the carbon fiber raw material in ethanol, adding an activator and reacting for 3 to 180 minutes, filtering out the carbon fiber and drying it; Then, the activated carbon fiber is dispersed in a mixed solution of n-butanol-deionized water and the pH value of the solution is adjusted to 2-4, and then fluorosilane is added, and the reaction is carried out for 2-36 hours under the conditions of an ultrasonic frequency of 5-40kHz and a temperature of 25-120°C; after the reaction is completed, the carbon fiber is filtered and dried to obtain fluorosilane-modified carbon fiber; The carbon fiber is one or more of asphalt-based carbon fiber, polyacrylonitrile-based carbon fiber and vapor-phase carbon fiber, with a diameter of 5-8 μm, an aspect ratio of 5-20, and a thermal conductivity of 500-1500 W / (m·K); the activator is one of acetic acid, nitric acid, sulfuric acid and hydrochloric acid, and the amount of the activator added is 5-50% of the volume of the carbon fiber raw material; the fluorosilane is one or more of trifluoropropyl methyl dimethoxy silane, trifluoropropyl trimethoxy silane, perfluorodecyl trimethoxy silane, perfluorooctyl triethoxy silane, perfluorodecyl triethoxy silane and heptadecafluorodecyl triethoxy silane; the amount of the fluorosilane added is 1-25% of the volume of the carbon fiber; The lubricating filler is one or more of graphite fluoride, molybdenum disulfide, polyetheretherketone, and polyimide; the size of the lubricating filler is 0.05-60 μm; The functional filler is one or more of aluminum oxide, aluminum nitride, carbon powder, boron nitride, nickel oxide and silicon carbide; the size of the functional filler is 20-500nm.
2. A bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber as claimed in claim 1, characterized in that: In the preparation method of the fluorosilane-modified carbon fiber, in the mixed solution of n-butanol-deionized water, the volume ratio of n-butanol to deionized water is 7.5:1 to 9.5:
1.
3. A bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber as claimed in claim 1, characterized in that: The mechanical blending is carried out in a double-shaft mixer, the shearing cutter speed of the stirring kettle is 200-4000 rpm, the overall rotation speed of the stirring kettle around the cantilever is 2-50 rpm, and the mixing time is 1-30 min.
4. A bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber as claimed in claim 1, characterized in that: The cold pre-pressing is carried out in a steel mold with upper and lower bidirectional loading, the pressing pressure is 25-45 MPa, and the holding time is 3-20 minutes.
5. A bearing lubricating material based on modified polytetrafluoroethylene and modified carbon fiber as claimed in claim 1, characterized in that: The sintering is carried out in a special polytetrafluoroethylene sintering furnace equipped with a rotating tray, the sintering temperature is 360-390° C., the time is 30-240 min, and the tray rotation speed is 5-50 rpm.
Citation Information
Patent Citations
Fluorosilane-modified carbon fiber enhanced polyvinylidene fluoride material and preparation method
CN105255077A
Filled modified polytetrafluoroethylene material as well as application and preparation method thereof
CN107177145A